ROOTING FIQH IN MODERN IJTIHAD: ADAPTING FIQH TO COMMUNITY NEEDS - Muhammad Ridho (Jurnal AL-AHKAM, 2022)
In the face of the changing position of Sharia in the modern state, the contemporary jurist found himself facing the task of covering huge developments with jurisprudential rulings. He devised a jurisprudential mechanism called "rooting," which allowed him to practice ijtihad and cross between the previously restricted sects. To prove the validity of Sharia for modern times and its compatibility with the time requirements, through which he hopes to restore Sharia to its ancient position. This research explains this new jurisprudential mechanism and the jurisprudential practice. It was carried out through examples of political and economic fields; the areas most affected by the new transformations are clear and influential in daily life. These examples reveal the nature of this jurisprudential practice that led to the logic governing the breaking of the Islamic jurisprudence and its adaptation to the age requirements. Although it represents a current between other jurisprudential currents, this practice reveals the predicament of the jurist in the modern world and the complex dilemma he faces. If he met the age requirements and legislated them by breaking the rules and logic of jurisprudence, he strengthened the weakness of the Sharia in influencing public life. If he stood in the face of these requirements, he maintained the isolation of Sharia. In both cases, the jurist consolidates the position of Sharia imposed by the modern state outside the influence of public life.